Exercise for rheumatoid arthritis of the hand - Williams, M; Srikesavan, C; Heine, P; Bruce, J; Brosseau, L; Hoxey-Thomas, N; Lamb, S (John Wiley & Sons, Ltd, 2018)
Rheumatoid arthritis is an inflammatory polyarthritis that frequently affects the hands and wrists. Hand exercises are prescribed to improve mobility and strength, and thereby hand function.To determine the benefits and harms of hand exercise in adults with rheumatoid arthritis.We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (the Cochrane Library), MEDLINE, Embase, CINAHL, AMED, Physiotherapy Evidence Database (PEDro), OTseeker, Web of Science, ClinicalTrials.gov and the World Health Organization International Clinical Trials Registry Platform (WHO ICTRP) up to July 2017.We considered all randomised or quasi-randomised controlled trials that compared hand exercise with any non-exercise therapy.We used standard methodological procedures as outlined by the Cochrane Musculoskeletal Group.We included seven studies involving 841 people (aged 20 to 94 years) in the review. Most studies used validated diagnostic criteria and involved home programmes.Very low-quality evidence (due to risk of bias and imprecision) from one study indicated uncertainty about whether exercise improves hand function in the short term (< 3 months). On a 0 to 80 points hand function test (higher scores mean better function), the exercise group (n = 11) scored 76.1 points and control group (n = 13) scored 75 points.Moderate-quality evidence (due to risk of bias) from one study indicated that exercise compared to usual care probably slightly improves hand function (mean difference (MD) 4.5, 95% confidence interval (CI) 1.58 to 7.42; n = 449) in the medium term (3 to 11 months) and in the long term (12 months or beyond) (MD 4.3, 95% CI 0.86 to 7.74; n = 438). The absolute change on a 0-to-100 hand function scale (higher scores mean better function) and number needed to treat for an additional beneficial outcome (NNTB) were 5% (95% CI 2% to 7%); 8 (95% CI 5 to 20) and 4% (95% CI 1% to 8%); 9 (95% CI 6 to 27), respectively. A 4% to 5% improvement indicates a minimal clinical benefit.Very low-quality evidence (due to risk of bias and imprecision) from two studies indicated uncertainty about whether exercise compared to no treatment improved pain (MD -27.98, 95% CI -48.93 to -7.03; n = 124) in the short term. The absolute change on a 0-to-100-millimetre scale (higher scores mean more pain) was -28% (95% CI -49% to -7%) and NNTB 2 (95% CI 2 to 11).Moderate-quality evidence (due to risk of bias) from one study indicated that there is probably little or no difference between exercise and usual care on pain in the medium (MD -2.8, 95% CI - 6.96 to 1.36; n = 445) and long term (MD -3.7, 95% CI -8.1 to 0.7; n = 437). On a 0-to-100 scale, the absolute changes were -3% (95% CI -7% to 2%) and -4% (95% CI -8% to 1%), respectively.Very low-quality evidence (due to risk of bias and imprecision) from three studies (n = 141) indicated uncertainty about whether exercise compared to no treatment improved grip strength in the short term. The standardised mean difference for the left hand was 0.44 (95% CI 0.11 to 0.78), re-expressed as 3.5 kg (95% CI 0.87 to 6.1); and for the right hand 0.46 (95% CI 0.13 to 0.8), re-expressed as 4 kg (95% CI 1.13 to 7).High-quality evidence from one study showed that exercise compared to usual care has little or no benefit on mean grip strength (in kg) of both hands in the medium term (MD 1.4, 95% CI -0.27 to 3.07; n = 400), relative change 11% (95% CI -2% to 13%); and in the long term (MD 1.2, 95% CI -0.62 to 3.02; n = 355), relative change 9% (95% CI -5% to 23%).Very low-quality evidence (due to risk of bias and imprecision) from two studies (n = 120) indicated uncertainty about whether exercise compared to no treatment improved pinch strength (in kg) in the short term. The MD and relative change for the left and right hands were 0.51 (95% CI 0.13 to 0.9) and 44% (95% CI 11% to 78%); and 0.82 (95% CI 0.43 to 1.21) and 68% (95% CI 36% to 101%).High-quality evidence from one study showed that exercise compared to usual care has little or no benefit on mean pinch strength of both hands in the medium (MD 0.3, 95% CI -0.14 to 0.74; n = 396) and long term (MD 0.4, 95% CI -0.08 to 0.88; n = 351). The relative changes were 8% (95% CI -4% to 19%) and 10% (95% CI -2% to 22%).No study evaluated the American College of Rheumatology 50 criteria.Moderate-quality evidence (due to risk of bias) from one study indicated that people who also received exercise with strategies for adherence were probably more adherent than those who received routine care alone in the medium term (risk ratio 1.31, 95% CI 1.15 to 1.48; n = 438) and NNTB 6 (95% CI 4 to 10). In the long term, the risk ratio was 1.09 (95% CI 0.93 to 1.28; n = 422).Moderate-quality evidence (due to risk of bias) from one study (n = 246) indicated no adverse events with exercising. The other six studies did not report adverse events.It is uncertain whether exercise improves hand function or pain in the short term. It probably slightly improves function but has little or no difference on pain in the medium and long term. It is uncertain whether exercise improves grip and pinch strength in the short term, and probably has little or no difference in the medium and long term. The ACR50 response is unknown. People who received exercise with adherence strategies were probably more adherent in the medium term than who did not receive exercise, but with little or no difference in the long term. Hand exercise probably does not lead to adverse events. Future research should consider hand and wrist function as their primary outcome, describe exercise following the TIDieR guidelines, and evaluate behavioural strategies.